Proposal to reject the names Cestrum subsessile, Solanum ambrosiacum, S. coronatum, S. diantherum, S. jubeba, S. multiangulatum and S. perianthomega (Solanaceae) from Vellozo´s Flora Fluminensis - Knapp, Sandra (2015)
Fil: Knapp, Sandra. Natural History Museum; Reino Unido